Anthropometric markers for fat obesity in Indonesian children aged 7 to 12 years in Yogyakarta Province, Indonesia - Hastuti, Janatin; Rahmawati, Neni Trilusiana (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Obesity must be determined precisely and accurately in order for intervention efforts to be more effective. Anthropometric measurement is accurate, simple, inexpensive, and non-invasive to perform, making it useful as a screening tool for body fat.Objective: The purpose of this study is to assess the performance of anthropometric indicators in assessing fat obesity in Indonesian children aged 7 to 12 years in Yogyakarta Province.Materials and Methods: Participants included 514 Javanese children (260 boys, 254 girls) aged 7-12 years who lived in Bantul and Kulon Progo Regencies and were healthy and willing to participate. Disabled children were excluded. Data were taken in 1998 including body weight, height, wrists, abdomen, waist and hip circumference, and skinfold thickness at biceps, triceps, subscapular, and suprailiac. Body mass index (BMI), body frame, waist-hip ratio (WHR), and waist-to-height ratio (WHtR) were further calculated. Body fat was estimated from skinfold thickness. Statistical analysis using ANOVA and Receiver Operating Characteristics (ROC) tests were performed.Results: The ANOVA test results showed that age was the main factor of significant variation (p<0.001) for all variables, while gender was significant for wrist circumference (p<0.05), body frame (p<0.05), and WHR (p<0.001). Gender and age are simultaneously significant only for height (p<0.001). ROC analysis showed that abdominal circumference in boys and waist circumference in girls had the widest area under the curve (AUC), while height had the smallest AUC in both genders. BMI had the highest AUC in boys (AUC= 0.984; p<0.001) and girls (AUC= 0.972; p<0.001).Conclusion: Abdominal circumference in boys and waist circumference in girls performed better than other anthropometric indicators for assessing body fat obesity. While, BMI outperforms all other anthropometric indices in both genders.